2020
DOI: 10.1186/s12964-020-00558-1
|View full text |Cite
|
Sign up to set email alerts
|

Blocking Connexin-43 mediated hemichannel activity protects against early tubular injury in experimental chronic kidney disease

Abstract: Background: Tubulointerstitial fibrosis represents the key underlying pathology of Chronic Kidney Disease (CKD), yet treatment options remain limited. In this study, we investigated the role of connexin43 (Cx43) hemichannelmediated adenosine triphosphate (ATP) release in purinergic-mediated disassembly of adherens and tight junction complexes in early tubular injury. Methods: Human primary proximal tubule epithelial cells (hPTECs) and clonal tubular epithelial cells (HK2) were treated with Transforming Growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 75 publications
(112 reference statements)
5
53
0
Order By: Relevance
“…When unbound, connexons form hemichannels through which molecules, e.g., adenosine triphosphate (ATP), can be released into the local extracellular space to influence neighbouring cells via activation of purinoreceptors [ 11 ]. Expression of the purinergic P2X7 receptor (P2X7R) is upregulated in the renal tubules of individuals with diabetic kidney disease [ 12 ] and has been heavily implicated in the progression of fibrosis both in the kidney [ 13 , 14 , 15 , 16 , 17 ] and in other tissue types [ 18 , 19 , 20 , 21 ]. Unsurprisingly, targeting purinergic signalling has received considerable attention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When unbound, connexons form hemichannels through which molecules, e.g., adenosine triphosphate (ATP), can be released into the local extracellular space to influence neighbouring cells via activation of purinoreceptors [ 11 ]. Expression of the purinergic P2X7 receptor (P2X7R) is upregulated in the renal tubules of individuals with diabetic kidney disease [ 12 ] and has been heavily implicated in the progression of fibrosis both in the kidney [ 13 , 14 , 15 , 16 , 17 ] and in other tissue types [ 18 , 19 , 20 , 21 ]. Unsurprisingly, targeting purinergic signalling has received considerable attention.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence links the aberrant expression and/or activity of connexins with various forms of CKD [ 12 , 23 , 24 , 25 , 26 ]. Initial studies by Abed et al reported that heterogenous (Cx43 +/− ) mice, with unilateral ureteral obstruction (UUO), exhibited reduced extracellular matrix (ECM) deposition and decreased inflammation [ 27 ], whilst the Cx43-specific mimetic, GAP-26, was able to inhibit monocyte adhesion and blunted the expression of collagen I in the renin transgene (RenTG) mouse model of renin-dependent CKD [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our result of higher expression of Cx43 in the medulla of P14 yotari mice might be in line with the increased Cx43 expression in nephropathy, where Cx43-mediated ATP release represented an initial trigger of early tubular injury via its actions on the adherents and tight junction complex. Thus, Cx43 might represent a novel target for intervention on tubulointerstitial fibrosis in CKD [ 23 ]. However, there is contradicting information on the function of Cx43 in kidney pathology: while Cx43 upregulation in the glomeruli was described in experimental rat glomerulonephritis and type 2 diabetes, its downregulation was observed in overt diabetic nephropathy).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Cx43 diminished renal fibrosis through c-Src [ 21 ] and reduced the progression of chronic kidney disease (CKD) in mice [ 22 ]. The blocking of Cx43 mediated hemichannel activity protected against early tubular injury in experimental CKD [ 23 ]. Additionally, Cx43 was involved in the progression of acute kidney injury by regulating intracellular oxidative status [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, more than 20 kinds of gap junction proteins have been identified ( Wang et al, 2018 ) and are widely present in human cells with channel-dependent and -independent functions ( Chen et al, 2019b ). Connexin 43 (Cx43) is abundantly expressed in kidney, and functions importantly in CKD via regulating a variety of processes ( Price et al, 2020 ). There is high Cx43 expression in animal kidney tissues subjected to acute kidney injury, and the mechanism may be related to oxidative stress-induced kidney injury ( Wang and Tong, 2015 ).…”
Section: Introductionmentioning
confidence: 99%